2014
DOI: 10.1021/jp503831p
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Structural Change in Iridium Complexes Studied by Electron Spin Resonance

Abstract: Iridium-based compounds are materials of great interest in the production of highly efficient organic light emitting diodes and several other applications. However, these organometallic compounds present relative low stability due to photodegradation processes still not well understood. In this work we investigated paramagnetic states induced by UV photoexcitation on iridium(III) bis[(4,6-fluorophenyl)-pyridinato-N,C2′]picolinate (FIrpic) and iridium(III)-tris(2-phenylpyridine) (Ir(ppy) 3 ) complexes dispersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…209 Using EPR, it is possible to study structural changes in emitting molecules (like FIrpic or Ir(ppy) 3 ) during UV excitation. 213 …”
Section: Chemical Analysis Techniquesmentioning
confidence: 99%
“…209 Using EPR, it is possible to study structural changes in emitting molecules (like FIrpic or Ir(ppy) 3 ) during UV excitation. 213 …”
Section: Chemical Analysis Techniquesmentioning
confidence: 99%
“…Entry 1 effectively demonstrates this principle with the device based on 1 exhibiting a remarkably long lifetime of 668 h. The authors attribute this stability to the relatively large calculated 3 MC-T 1 energy gap for 1 [ 23 ]. Theory and experimental observations have implicated 3 MC states in an elongation of the N pyridyl -Ir bond of the C^N ligands of [Ir(C^N) 2 (N^N)] + complexes, which accounts for the efficient non-radiative quenching resulting from these states [ 40 ]. In addition, work on ruthenium(II) complexes has suggested that this bond lengthening/breaking process within the 3 MC state introduces a free coordination site that allows small molecules such as water to coordinate to the metal, quenching the emission and leading to degradation products within the device [ 13 , 41 ].…”
Section: [Ir(ppy) 2 (Bpy)](pf 6 mentioning
confidence: 99%
“…In addition to problems common to all OLEDs, blue phosphors present additional challenges, 100 especially thermally accessible non-radiative metal centred states. 101,102 FIrpic is further disadvantaged because of chemical complication arising from its chemical structure.…”
Section: Stabilitymentioning
confidence: 99%